STRATEGI PENGEMBANGAN EKONOMI LOKAL MELALUI KAWASAN DESA WISATA BERBASIS KOMODITAS UNGGULAN KOPI LIBERIKA (KBA) DI DESA KUMPAI BATU ATAS KECAMATAN ARUT SELATAN KABUPATEN KOTAWARINGIN BARAT - Rizkiyah, Noor; Shofiyah, Shofiyah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The development of the local economy through the concept of a tourism village based on agricultural commodities is a manifestation of a sustainable economy, which is not only creating business opportunities based on the development of agricultural products but also related to community empowerment and sustainability so that they are ready to be competitive in the global market. This study aims to determine the advantages of Kumpai Batu Atas village, South Arut sub-district, West Kotawaringan Regency in developing KBA liberika coffee, using descriptive qualitative method with SWOT approach. Based on the determination of internal and external factors which are then combined so that it can be formulated 1) Increasing land productivity for liberika coffee cultivation through the support of groups and local governments by creating a tourism village concept based on agricultural products to encourage local economic improvement 2) Optimizing cultivation activities by creating added value through strengthening capital 3) Increasing knowledge of technology-minded coffee farmers and local governments as providers of appropriate technology, so that KBA liberika coffee is able to be competitive. 4) Development of sustainable technology in eradicating plant-disturbing organisms and local governments to create regional clusters based on land suitability.